TEKNIK MANAJEMEN HUMAS DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM - Mulyono Mulyono (Ulumuna, 2011)
Abstract: Islamic Education Institute (IEI) is grown and developed by, through the initiative, and for the shake of Muslim communities’ demands, so hat the existence of public relations management on the development of IEI becomes important. This article aims to provide concepts of techniques of public relations management in the development of IEI in Indonesia, as well as how to apply it, problems faced, and how to solve the problems. The results of this study are expected to be able to broaden insight of managers of IEI in order to make public relations programs effectively and efficiently operational, and to realize the development of IEI in a broad sense. Abstrak:  Lembaga Pendidikan Islam (LPI) ditumbuhkan dan dikembangkan oleh, melalui prakarsa, dan untuk memenuhi tuntutan masyarakat muslim, sehingga eksistensi manajemen humas pada pengembangan LPI menjadi sangat penting. Artikel ini bertujuan untuk memberikan tawaran konsep teknik manajemen humas dalam pengembangan LPI di Indonesia; bagaimana menerapkan konsep itu, problem-problem yang dihadapi, dan bagaimana memecahkan problem itu. Hasil kajian ini diharapkan dapat memperluas wawasan para pengelola LPI sehingga mereka dapat mengoperasionalkan program humas secara efektif dan efisien, dan mewujudkan perkembangan LPI dalam arti luas.